Profile of multidrug-resistant bacteria causing urinary tract infections in inpatients and outpatients in Jakarta and Tangerang - Rosana, Yeva; Herliyana, Lina; Krisandi, Grady; Anggraini Suwarsono, Erike (Faculty of Medicine, Universitas Trisakti, 2023)
Background Urinary tract infections (UTIs) caused by bacteria occupy the second highest rank of common infectious diseases in the world. Empirical use of antibiotics may give rise to multidrug-resistant (MDR) bacteria because of irrational prescription. Choice of antibiotics to treat UTIs is limited because of MDR bacteria. Thus, this study was conducted to investigate the bacterial antibiotic susceptibility patterns in inpatients and outpatients in Jakarta and Tangerang. Methods Bacterial isolates were obtained from midstream urine specimens from 43 inpatients and 43 outpatients with UTIs in Jakarta and Tangerang. Bacteria were isolated on blood and MacConkey agar media using colony count method. Isolate identification and their susceptibility patterns were performed using VITEK2 compact system according to manufacturers’ instructions. Data were analyzed using Chi-square test. Results A total of 89 bacterial isolates consisting of 15 bacterial species were successfully isolated from 86 specimens. Gram-negative bacteria were the most common etiology of UTIs in inpatients and outpatients. MDR bacteria were found in 52 of the 89 isolates. ESBL-producing E. coli was the most common MDR bacteria. ESBL-producing E. coli and other MDR bacteria showed good susceptibility to ertapenem, meropenem, amikacin, and tigecycline. There were no significant differences regarding the MDR bacterial count in inpatients and outpatients (p=0.521). Conclusion E. coli was found to be the most common MDR bacteria causing UTIs in inpatients and outpatients in Jakarta and Tangerang. Higher resistance to many antibiotics was found in MDR bacterial isolates in inpatients compared to outpatients. MDR bacteria in outpatient UTIs were highly resistant to commonly used antibiotics.